Estimation of Tsunami Arrival Time and Run-up Height Using The Cornell Multi-Grid Coupled Tsunami Model (COMCOT) at Ujung Bulu and Bira Beaches, Bulukumba Regency, Indonesia - Chaerul, Muhammad; Muh. Imran Tahir; Anshari, Erwin (UIR PRESS, 2026)
This study aims to estimate tsunami arrival times and wave heights at Ujung Bulu Beach and Bira Beach, Bulukumba Regency, using numerical simulations with the Cornell Multi-grid Coupled Tsunami Model (COMCOT). Two potential tsunamigenic earthquake scenarios were considered: the West Nusa Tenggara segment of the Flores Back-Arc Thrust (Mw 7.5) affecting Ujung Bulu District, and the eastern segment of the Selayar Fault (Mw 7.2) impacting Bira Beach in Bontobahari District.Modeling results indicate that tsunami arrival times at Ujung Bulu range from approximately 46 minutes at the coastline to 56 minutes inland, with modeled wave heights varying between 0.02 and 1.96 m. In contrast, Bira Beach experiences significantly shorter arrival times, ranging from 3 to 6 minutes, with wave heights between 0.10 and 10.00 m. The reported tsunami heights represent the maximum modeled water surface elevation above mean sea level at each location.These results highlight the near-field tsunami hazard at Bira Beach and the moderate but widespread inundation potential in Ujung Bulu District. The findings provide important implications for disaster risk reduction in Bulukumba Regency, including improvements in early warning dissemination, evacuation planning, and community preparedness. Nevertheless, the results are subject to uncertainties associated with earthquake source parameterization, bathymetric resolution, and numerical modeling assumptions.